Iron deficiency as risk factor for febrile convulsion and the association of iron deficiency anemia and febrile convulsion - Mohammad Neyazuddin; Rajendra Nistane (Asian Journal of Medical Sciences, 2022)
Background: Febrile seizure occurs in 2–5% of neurologically healthy infants and children. The recurrence of febrile seizures is 30% after single episode, 50% after 2 or more episodes, and 50% when febrile seizures occur in infants. Their incidence of febrile seizures in India is 10–17% which is higher than in developed countries (2–7%). Aims and Objectives: The purpose of this study was to evaluate iron deficiency (ID) as a risk factor for febrile convulsion and the association of ID anemia with febrile convulsions. Materials and Methods: This was an observational case–control study conducted in tertiary care center in central India between December 2019 and June 2021. All patients with febrile seizures taken as cases and control from similar age group with febrile illness. Body temperature of children in both the groups was measured and recorded. The blood tests of complete blood count, serum iron, and TIBC were performed. Results: In the present study, mean age was 2.33 years in case and mean age was 2.204 years in control. The mean hemoglobin levels were 8.25±1 g/dL in the febrile seizure case group and 9.86±1.49 g/dL in the control group; and their statistical difference was significant. Serum ferritin values was significantly lower among cases group than the control group. The average of MCV, MCH, and MCHC for the case group was less than that of the control group. The present study also demonstrates an association between ID and febrile seizures. Thus, ID is one of the possible risk factors for febrile seizures. Conclusion: The present study showed that hemoglobin, MCV, serum ferritin, and serum iron levels are significantly lower in children suffering from febrile seizures, suggesting that a low iron status has an important role in children with febrile seizures. Thus, ID is predictor for febrile convulsion.